Surface texture enhancement of SLS processed turbine blades using a mix of flexible media and abrasives - Titus, Matthew (Department of Mechanical Engineering, 2023)
Additive manufacturing technologies such as Selective Laser Sintering of Grade 5 Titanium has been used extensively within the aerospace industry as it allows for the fabrication of complex shapes with minimal material wastage. With the increased use of complex shapes, newer polishing technologies need to be developed to accommodate the fabrication technological advancements. This dissertation proposes a novel abrasive flow polishing technology that can lower polishing times as well as limiting damage that polishing may have on a component due to excessive forces. This is achieved by the addition of a flexible media to the abrasive particles to achieve more desirable properties of the polishing media. The technology has been partially developed with further design requirements being investigated by means of explicit dynamic simulations within the Ansys package. The simulations include an asperity made of Grade 5 titanium, a SiC abrasive particle and, an HDPE particle as the flexible media. These simulations have tested process parameters such as abrasive size, asperity size and impact velocity. These simulations have shown that addition of the flexible media can increase the material removal rate of process by up to 200% due to a vibratory motion that was observed of the abrasive particle. These results are promising in showing that the proposed abrasive flow polishing technology can improve the material removal rate of the current aero lapping technology due to the addition of the flexible media. Preliminary testing for this technology has shown that the developed system is within a 22% performance range of similar literature. However, the verification of these simulations and findings needs to be completed through thorough testing of the physical technology.